An Optimized Solution to Long‐Distance Flight Routes Under Extreme Cosmic Radiation - Dabin Xue; Jian Yang; Zhizhao Liu; Bing Wang (Space Weather)
Abstract During extraordinary space weather, cosmic radiation can be significant enough to pose a threat to aircrew health. Traditional methods of reducing massive cosmic radiation exposure include flight cancellation, lowering flying altitudes, and flight rerouting. However, flight cancellation can result in additional financial expenditures, while lowering flight altitudes and rerouting can consequently cause more fuel consumption or even violation of airspace rights. As a result, we use a multi‐objective optimization model to assign optimal flight altitude and speed to reduce the overall weighted sum of cosmic radiation and fuel consumption. The simulation scenario is based on a space weather event with dramatically increased cosmic radiation that occurs during a routine international flight from Tokyo to London. Our results show that the proposed model can reduce fuel consumption while satisfying cosmic radiation limits recommended by the Council of the European Union if the forecasts of cosmic radiation are sufficiently accurate. In addition, a Pareto frontier is provided as a tactical air traffic management guideline. Our study provides insight into future policymaking for air transportation during harsh space weather conditions.